Microbiota and mycobiota in bronchoalveolar lavage fluid of silicosis patients - Linshen Xie; Xiaoyan Zhang; Xiaosi Gao; Linyao Wang; Yiyang Cheng; Shirong Zhang; Ji Yue; Yingru Tang; Yufeng Deng; Baochao Zhang; Xun He; Mingyuan Tang; et al. (Journal of Occupational Medicine and Toxicology, 2023)
Abstract Background The contribution of bronchoalveolar lavage fluid (BALF) microbiota and mycobiota to silicosis has recently been noticed. However, many confounding factors can influence the accuracy of BALF microbiota and mycobiota studies, resulting in inconsistencies in the published results. In this cross-sectional study, we systematically investigated the effects of “sampling in different rounds of BALF” on its microbiota and mycobiota. We further explored the relationship between silicosis fatigue and the microbiota and mycobiota. Methods After obtaining approval from the ethics board, we collected 100 BALF samples from 10 patients with silicosis. Demographic data, clinical information, and blood test results were also collected from each patient. The characteristics of the microbiota and mycobiota were defined using next-generation sequencing. However, no non-silicosis referent group was examined, which was a major limitation of this study. Results Our analysis indicated that subsampling from different rounds of BALF did not affect the alpha- and beta-diversities of microbial and fungal communities when the centrifuged BALF sediment was sufficient for DNA extraction. In contrast, fatigue status significantly influenced the beta-diversity of microbes and fungi (Principal Coordinates Analysis, P = 0.001; P = 0.002). The abundance of Vibrio alone could distinguish silicosis patients with fatigue from those without fatigue (area under the curve = 0.938, 95% confidence interval [CI] 0.870–1.000). Significant correlations were found between Vibrio and haemoglobin levels (P < 0.001, ρ = -0.64). Conclusions Sampling in different rounds of BALF showed minimal effect on BALF microbial and fungal diversities; the first round of BALF collection was recommended for microbial and fungal analyses for convenience. In addition, Vibrio may be a potential biomarker for silicosis fatigue screening.